A writer's resource : - Maimon, Elaine P (McGraw-Hill, 2003)
The second edition of A Writer's Resource draws on its authors' 20 years of research into writing in college and provides the most extensive technological support available, forming an indispensable resource for learning, writing, researching, and editing. The second edition features a stonger focus on visual rhetoric, new documentation flowcharts, a new chapter on multimedia assignments, enhanced coverage of note-taking and plagiarism, new online peer review utilities (as well as course management utilities for instructors), and more!